2020
DOI: 10.1177/0961203320941941
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in the intensive care unit: a systematic review

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease with heterogeneous pathophysiologic mechanisms and diverse clinical manifestations. SLE is a frequent cause of intensive care unit (ICU) admissions. Multiple studies with controversial findings on the causes, evolution and outcomes of ICU-admitted patients with SLE have been published. The aim of this paper is to review the literature reporting the clinical characteristics and outcomes, such as mortality and associated factors, in such patients. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 93 publications
(193 reference statements)
0
16
1
Order By: Relevance
“…Our study's mortality rate was even lower than those shown in some adult cohorts, where mortality rates varied from 18 to 78.5%. 34 However, the causes of mortality differed from ours. Only 11% of all deaths were attributed to AID activity in comparison to more than 80% of our deaths explained by this variable.…”
Section: Discussioncontrasting
confidence: 66%
“…Our study's mortality rate was even lower than those shown in some adult cohorts, where mortality rates varied from 18 to 78.5%. 34 However, the causes of mortality differed from ours. Only 11% of all deaths were attributed to AID activity in comparison to more than 80% of our deaths explained by this variable.…”
Section: Discussioncontrasting
confidence: 66%
“…These results reinforce previous findings that lupus patients with episodes of bacteremia have poor outcome. 16 According to previous studies, the most common cause of ICU admission for patients with SLE was infection, [17][18][19] and those who were admitted to ICU due to infection had showed substantially longer ICU stay, higher Acute Physiology and Chronic Health Evaluation (APACHE) II score and higher mortality compared with SLE with noninfectious causes. 20 Considering its deteriorating effect on treatment outcomes and prognosis of SLE, identifying risk factors for BSI during immunosuppressive treatment is essential to establish an appropriate surveillance and prophylaxis strategy against BSI in patients with SLE receiving mediumto-high dose glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…What are the recommendations for management of infection? [40][41][42][43][44][45] Mean rate ± SD: 8.81 ± 0.39, % of agreement: 100%, LOE: H…”
Section: Pulmonary Hemorrhagementioning
confidence: 99%